RULER'S DISCRIMINATION AGAINST CHILDREN IN KABA RAMBUN PAMENAN - Febrina, Liga; Novianti, Hasmi (Jurnal Ilmu Pendidikan Ahlussunnah, 2024)
Literary works are creative works of art that tell about events or incidents experienced by humans. Regional literature is literature that reflects regional culture contained in regional literature. The problem of the habits of those in power which are contrary to the demands of humanity and society, shows the arbitrary actions of someone in power, without first thinking and considering the fate of the people around him, including children abandoned by their parents. Discrimination carried out by a ruler against minors takes the form of physical discrimination and psychological discrimination, the factors that cause discrimination, and the implications of this discrimination for children. The aim of the researcher in conducting this research is so that the researcher can obtain results about the discrimination that occurs in the Rambun Pamenan kaba.